Pertanggungjawaban Bank terhadap Nasabah Pasca-Merger: Studi Kasus Kenaikan Kolektabilitas Kredit Akibat Integrasi Sistem - Aditama Candra Kusuma (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
The rapid growth of Indonesia’s banking industry has encouraged various corporate actions, such as mergers, to enhance efficiency and competitiveness. However, post-merger system integration often creates issues for customers, particularly the increase in credit collectability caused by data migration errors. This study aims to analyze the legal protection and liability of banks toward customers adversely affected by the merger process. The research employs a normative juridical approach through legislation review and case study analysis. The findings indicate that customer legal protection operates both preventively and repressively. Preventive protection is regulated under the Financial Services Authority Regulation (POJK) No. 6/POJK.07/2022, emphasizing transparency, education, and data security principles. Meanwhile, repressive protection is carried out through internal bank complaint mechanisms, the Financial Services Alternative Dispute Resolution Institution (LAPS SJK), and civil lawsuits under Articles 1365 and 1243 of the Indonesian Civil Code. The study concludes that banks are legally responsible for restoring customers’ rights by correcting SLIK data, issuing clarification letters, and providing material and immaterial compensation. Upholding prudential principles and consumer protection is essential to maintaining public trust in the post-merger banking system.